2000
DOI: 10.3758/bf03212083
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between decision rules and perceptual representation in multidimensional perceptual categorization

Abstract: This article examines the relation between changing categorization decision rules and the nature of the underlying perceptual representation. Observers completed a matching task that required them to adjust the length and orientation of a single line stimulus until they perceived it to "match" a second line stimulus (Alfonso-Reese, 1996. The same observers then completed four categorization tasks with the same stimuli. Data from the matching task were used to estimate a perceptual representation for each stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 48 publications
3
40
1
Order By: Relevance
“…The ability to perform these tests draws on more than 3 decades of theoretical and empirical advances (based on critical contributions from Schweickert, 1978Schweickert, , 1983Schweickert et al, 2000;Townsend, 1972Townsend, , 1974Townsend & Ashby, 1978;Townsend & Nozawa, 1995;and Townsend & Schweickert, 1989, among others). It is our hope that this study, like others demonstrating the application of experimental methodologies with strong links to formally specified theories of psychological information and processes (e.g., Ashby, Alfonso-Reese, Turken, & Waldron, 1999;Maddox & Bogdanov, 2000;Thomas, 1996;Townsend & Nozawa, 1995;Wenger & Ingvalson, 2002Wenger & Townsend, 2001), will lead to strong tests of a variety of hypotheses and, thus, enliven the ongoing empirical and theoretical discussions of facial cognition. S(t) ϭ 1 Ϫ F(t) and F(t) ϭ 1 Ϫ S(t).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to perform these tests draws on more than 3 decades of theoretical and empirical advances (based on critical contributions from Schweickert, 1978Schweickert, , 1983Schweickert et al, 2000;Townsend, 1972Townsend, , 1974Townsend & Ashby, 1978;Townsend & Nozawa, 1995;and Townsend & Schweickert, 1989, among others). It is our hope that this study, like others demonstrating the application of experimental methodologies with strong links to formally specified theories of psychological information and processes (e.g., Ashby, Alfonso-Reese, Turken, & Waldron, 1999;Maddox & Bogdanov, 2000;Thomas, 1996;Townsend & Nozawa, 1995;Wenger & Ingvalson, 2002Wenger & Townsend, 2001), will lead to strong tests of a variety of hypotheses and, thus, enliven the ongoing empirical and theoretical discussions of facial cognition. S(t) ϭ 1 Ϫ F(t) and F(t) ϭ 1 Ϫ S(t).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the effects of learning can be examined (Maddox, 2002). Finally, a more complete understandingof auditory stimulus processing can be obtained by modeling performance simultaneously across these two different, but related, tasks (Ashby & Lee, 1991;Maddox & Ashby, 1996; see also Maddox & Bogdanov, 2000).…”
Section: Future Directionsmentioning
confidence: 99%
“…Two models that do this are decision bound theory (Ashby & Gott, 1988;Ashby & Maddox, 1994) and the extended generalized context model (EGCM; Lamberts, 1995Lamberts, , 1998Lamberts, , 2000. Maddox and colleagues have conducted a series of experiments using decision bound theory to examine the perceptual effects of attention in categorization (Maddox, 2001;Maddox & Bogdanov, 2000;Maddox & Dodd, 2003). These studies have shown that category structure-and hence, the type of decision required during categorizationappears to mediate any effects of attention on perception.…”
mentioning
confidence: 99%